US Policy Responses to the Covid-19 Pandemic and Sectoral Stock Indices: A Fractional Integration Approach - Guglielmo Maria Caporale; Luis A. Gil-Alana; Emmanuel Joel Aikins Abakah (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper uses fractional integration methods to assess the impact of US policy responses (containment and health measures, income support policy, debt-relief policy, changes in the Effective Federal Funds Rate, monetary and fiscal announcements) to the COVID-19 pandemic on US sectoral stock indices for Technology, Telecom, Health Care, Real Estate, Consumer Staples, Consumer Discretionary, Industrials, Basic Materials, Energy and Utilities from 1 January 2020 to 11 June 2021. The results provide evidence of mean reversion for seven sectoral stock indices (Consumer Discretionary, Consumer Staples, Health, Industrials, Technology, Telecom and Utilities), with orders of integration significantly below (though close to) 1 under the assumption of white noise errors. By contrast, three indices (Basic Materials, Energy and Real Estate) are found to be highly persistent (d ≥ 1), with shocks having permanent effects. As for the policy responses, it appears that the containment and health restrictions, income support policy, and debit relief policy have had no impact. By contrast, changes in the Effect Federal Funds Rate have had a significant and positive effect on all sectors except Energy and Industrial, and similarly monetary and fiscal announcements have had a positive and significant effect in most cases. Finally, the higher mortality rate caused by the Covid-19 pandemic has affected negatively most sectoral stock indices.
Keywords: C22; C32; G15; 330; Covid-19 pandemic; US sectoral stock indices; fractional integration